Effect of nutritional therapy in Emery–Dreifuss muscular dystrophy: a case report - Valoriani, Filippo; Pinelli, Giovanni; Gabriele, Silvia; Menozzi, Renata (Frontiers in Nutrition, 2024)
Emery-Dreifuss Muscular Dystrophy (EDMD) is a rare, inherited human disease. Similarly to other neuromuscular dystrophies, EDMD is clinically characterized by muscle atrophy and weakness, multi-joint contractures with spine rigidity and cardiomyopathy. In time, muscular weakness can lead to dysphagia and severe lowering of Body Mass Index (BMI), worsening the prognosis.We present the case of a young male affected by EDMD, admitted to the hospital for a pneumothorax in a severe state of undernourishment. The patient was treated with Total Parenteral Nutrition (TPN) with Smofkabiven ® , added with micronutrient supplementations (vitamins, and trace elements), and with minimal enteral nutrition through food. Within a year the patient gained 8.5 kg and kept his body weight stable for the 6 years of the follow up. Here we show that TPN ensures the nutritional requirements of EDMD patient in a safe and well-tolerated manner, allowing a considerable and stable improvement in nutritional status, which has a positive impact on the disease itself and the patients' quality of life.